Effects of integrated biocontrol on bacterial wilt and rhizosphere bacterial community of tobacco - Yun Hu (Nature Portfolio, 2021)
Abstract Bacterial wilt as a soil-borne disease was caused by Ralstonia solanacearum, and seriously damages the growth of tobacco. Integrated biocontrol method was explored to control bacterial wilt. Nevertheless, the long-term effects of the integrated biocontrol method on soil bacterial community, soil physicochemical properties and the incidence of bacterial wilt are not well understood. In this study, B. amyoliquefaciens ZM9, calcium cyanamide and rice bran were applied to tobacco fields in different ways. The disease index and incidence of tobacco bacterial wilt (TBW), soil physicochemical properties, colonization ability of B. amyoliquefaciens ZM9, and rhizopshere bacterial community were investigated. The results showed that the integrated application of B. amyoliquefaciens ZM9, rice bran and calcium cyanamide had the highest control efficiency of TBW and bacteria community diversity. Additionally, the integrated biocontrol method could improve the colonization ability of B. amyoliquefaciens ZM9. Furthermore, the integrated biocontrol method could effectively suppress TBW by regulating soil physicochemical properties, promoting beneficial bacteria and antagonistic bacteria of rhizopshere soil. This strategy has prospect of overcoming the defects in application of a single antagonistic bacteria and provides new insights to understand how to improve the colonization capacity of antagonistic bacteria and control efficacy for TBW.